English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-05-24 07:17:22 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

√6a(√3a+√2a) = (√6a x √3a) + (√6a x √2a) = √18a + √12a
= √(9 x 2)a + √(4 x 3)a = 3√2a + 2√3a

2007-05-24 07:36:15 · answer #1 · answered by blueskies 7 · 1 0

square root of 6a times the square root of 3a +square root of 6a time the square root of 2a

2007-05-24 07:27:14 · answer #2 · answered by blue eyed beauty 1 · 0 0

= √18a + √12a
= 3.√2 a + 2.√3 a
= (3.√2 + 2.√3).a

2007-05-24 10:19:12 · answer #3 · answered by Como 7 · 1 0

sqrt6a(sqrt3a+sqrt2a)
=sqrt(18a^2)+sqrt(12a^2)
=sqrt9*2a^2+sqrt4*3a^2
=3a sqrt2+2asqrt3
=a(3sqrt2+2sqrt3)

2007-05-24 07:54:54 · answer #4 · answered by alpha 7 · 0 0

fedest.com, questions and answers